The influences of cooperative climate, competitive climate and customer empowerment on service creativity. (November 2021) - Lee, Tingko; Sam Liu, Chih-Hsing; Li, Pei-Hsun
Abstract: To extend the relationship between customer empowerment and creativity, this study explores the mediating effects of intrinsic and extrinsic motivations (individual level). The study aims to clarify whether cooperative and competitive climates influence service creativity through intrinsic and extrinsic motivations (across level). A matching sample of 333 coaches and customers from 30 stores in the fitness industry was used to examine the study hypotheses by employing Mplus 8.3 statistical software. The results show that (1) customer empowerment and cooperative climate have significant positive effects on service creativity (that is, the service creativity of coaches); (2) the intrinsic motivation of coaches mediates the relationship between customer empowerment and service creativity; and (3) the intrinsic motivation of coaches mediates the relationship between cooperative climate and service creativity, but the mediating mechanism of extrinsic motivation does not exist in the relationship between competitive climate and service creativity.